Structural Optimization of cable-stayed bridges considering the action of permanent and transitory loads - Santos, Carolina Almeida Novaes dos (2019)
Cable-stayed bridges are complex structures with several advantages such as aesthetical appeal, economic use of materials, and efficient construction method. Due to these advantages and the extensive knowledge gained from projects over the years, longer cable-stayed bridges are being constructed. As span lengths increase, structures become more flexible, which makes the accurate evaluation of wind loads critically important in the design of cable-stayed bridges. In this thesis, the developed numerical model is based on the Finite Element Method (FEM), the Real Coded Genetic Algorithm (RCGA), and the Discrete-Phases Design Approach. The latter classifies variables into two categories: (i) main variables are optimized directly by the RCGA, and (ii) secondary variables are indirectly optimized by the discrete phases. Buffeting wind loads are considered as equivalent static forces, which were validated through a theoretical-experimental correlation. This powerful tool is used to assess the importance of considering truck together with uniformly distributed live loads, as well as wind buffeting loads and various aeroelastic instabilities in the design optimization process. Results show that the most critical load combination include the wind effect, and that the critical wind velocities of aeroelastic phenomena play a significant role for high values of basic wind speeds.